Validation of organizational ecology management model in education - ali mahdiyar; seyede khadijeh moafi madani; esmaeil kazempour (مجله علوم روانشناختی)
Background: Today, environmental changes and organizations' reactions to these changes are one of the main problems in understanding the behavior of organizations, which requires a new management method. Therefore, in order to maintain the balance of internal needs and adapt to the environmental conditions, the education and training organization needs a management in which the causal, contextual, intervening conditions, consequences and organizational ecology management strategies are carefully examined. To help improve organizational behavior and interactions between organization members and the natural environment Aims: The current research was conducted with the aim of validating the management model of organizational ecology in Tehran education. Methods: The method of the current research was correlation with confirmatory factor analysis and structural equation modeling. The research community included all the education managers of Tehran in 2023, of which 400 were selected using the available method. The measurement part of the paradigmatic model was done based on confirmatory factor analysis with AMOS software and the structural part of the model was done using structural equations based on partial least squares with PLS-3 software. Results: The results showed that the research model has a good fit. In the paradigmatic model of organizational ecology management, causal conditions are based on phenomenon (P< 0.001, β= 0.817), phenomenon-oriented on strategies (P< 0.001, β= 0.497), strategies on consequences (P< 0.001), β= 0.361), intervening conditions have an effect on the results (P< 0.001, β= 0.284) and background factors have an effect on the results (P< 0.001, β= 0.337). Conclusion: Organizational ecology management is a basic solution for the development of successful and flexible interactions of the employees of the education and training organization with each other and with the environment, and managers should, by knowing the effective components of organizational ecology management, take it into account in their planning. pay attention.